Evaluating Mathematics Instruction under the Independent Curriculum: A Stake Model Analysis from Yogyakarta Junior High Schools - Nurhamidah Manullang; Jailani Jailani (AL-ISHLAH: Jurnal Pendidikan, 2025)
The Independent Curriculum (Kurikulum Merdeka) in Indonesia aims to promote student-centered, differentiated learning. However, its implementation in mathematics education presents various challenges, particularly in planning, instruction, and assessment. This study employed a quantitative descriptive approach supported by qualitative data. The Stake evaluation model—comprising antecedents (planning), transactions (implementation), and outcomes (results)—was used to assess the curriculum's effectiveness in 12 junior high schools in Yogyakarta. Data were collected through document analysis of teaching modules and assessment tools, classroom observations, and evaluation of student learning outcomes. The planning phase showed that teaching modules in the independent sharing and changing categories were rated “good” (75.12% and 66.87%, respectively), while the independent learning category achieved a “very good” score (81.45%). In the implementation phase, independent sharing scored 75.90% (“good”), and both independent changing and learning categories scored 89.74% (“excellent”). However, in the assessment phase, scores were lower: 51.43% for independent sharing, 60.00% for independent changing, and 61.67% for independent learning, all falling into the “fairly good” category. While the planning and implementation stages align well with curriculum standards, assessment practices remain inconsistent and underdeveloped. The Independent Curriculum has been implemented adequately in mathematics learning across different categories, but the assessment component requires targeted improvement. Strengthening teacher capacity in assessment design and understanding of differentiated evaluation strategies is recommended to optimize learning outcomes.